A Solution to Cooperative Area Coverage Surveillance for a Swarm of MAVs. (3rd December 2013) - Zheng-Jie, Wang; Wei, Li
Considering that coverage evaluation and control is one of the critical areas in surveillance, in this study we use deployment entropy to assess the coverage quality of a swarm of micro air vehicles (MAVs). Depending on the evaluation result of deployment entropy, we also develop a two-level redeployment algorithm to cope with the MAVs' redeployment problem for maximizing coverage. With the goal of distributing the MAVs evenly over the interested region, we divide the redeployment process into two levels: the global level and the local level. We propose a strategy of MAV redeployment for maximizing the deployment entropy at both levels. From numerical simulation, results show that by computing the value of deployment entropy, it is possible to evaluate the distribution of the MAVs' network in a wide area and the two-level algorithm can improve the sensing coverage of MAVs.